Stem Cells for Cutaneous Wound Healing. (2nd June 2015) - Kirby, Giles T. S.; Mills, Stuart J.; Cowin, Allison J.; Smith, Louise E.
Abstract : Optimum healing of a cutaneous wound involves a well-orchestrated cascade of biological and molecular processes involving cell migration, proliferation, extracellular matrix deposition, and remodelling. When the normal biological process fails for any reason, this healing process can stall resulting in chronic wounds. Wounds are a growing clinical burden on healthcare systems and with an aging population as well as increasing incidences of obesity and diabetes, this problem is set to increase. Cell therapies may be the solution. A range of cell based approaches have begun to cross the rift from bench to bedside and the supporting data suggests that the appropriate administration of stem cells can accelerate wound healing. This review examines the main cell types explored for cutaneous wound healing with a focus on clinical use. The literature overwhelmingly suggests that cell therapies can help to heal cutaneous wounds when used appropriately but we are at risk of clinical use outpacing the evidence. There is a need, now more than ever, for standardised methods of cell characterisation and delivery, as well as randomised clinical trials.